Biological activities of lignoids from amazon Myristicaceae species: Virola michelii, V. mollissima, V. pavonis and Iryanthera juruensis - Morais, Sabrina K.R.; Teixeira, Ana F.; Torres, Zelina Edos S.; Nunomura, Sergio Massayoshi; Yamashiro-Kanashiro, Edite Hatsumi G.; Lauletta Lindoso, José Angelo; Yoshida, Massayoshi (Journal of the Brazilian Chemical Society, 2009)
This work revisits the fruits of Iryanthera juruensis and Virola pavonis and the leaves from V. michelii, as well as describing a study of the fruits of V. mollissima. In I. juruensis aryltetraline neolignan (1) and tetrahydrofuran neolignan (2), were found while from V. pavonis neolignans of benzofuran type (6-9), the tetrahydrofuran type (2, 11-13, 17) and the biphenyl type (10), in addition to diastereoisomers of the 8.O.4'-oxyneolignan type (14 and 15) and others were isolated. The V. mollissima accumulates the aryltetralone neolignan 4 and its seco derivative (5). The lignoids 1 and 2 obtained from I. juruensis arils possess antileishmanial activity against the promastigote form of Leishmania amazonensis. ©2009 Sociedade Brasileira de Química.